Influenza A virus replicates productively in primary human kidney cells and induces factors and mechanisms related to regulated cell death and renal pathology observed in virus-infected patients - Koch, Benjamin; Shehata, Mahmoud; Müller-Ruttloff, Christin; Gouda, Shady A.; Wetzstein, Nils; Patyna, Sammy; Scholz, Anica; Schmid, Tobias; Dietrich, Ursula; Münch, Christian; Ziebuhr, John; Geiger, Helmut; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Influenza A virus (IAV) infection can cause the often-lethal acute respiratory distress syndrome (ARDS) of the lung. Concomitantly, acute kidney injury (AKI) is frequently noticed during IAV infection, correlating with an increased mortality. The aim of this study was to elucidate the interaction of IAV with human kidney cells and, thereby, to assess the mechanisms underlying IAV-mediated AKI. We demonstrate productive replication of low and highly pathogenic IAV strains on primary and immortalized nephron cells. Comparison of our transcriptome and proteome analysis of H1N1-type IAV-infected human primary distal tubular cells (DTC) with existing data from H1N1-type IAVinfected lung and primary trachea cells revealed enrichment of specific factors responsible for regulated cell death in primary DTC, which could be targeted by specific inhibitors.